The effects of financial risks on financial performance of commercial banks in Nigeria - Ebenezer, Olalere Oluwaseyi. author (School of Business Innovation & Technopreneurship, 2017)
Given limited resources and time, the research scope is to study the effect of financial risk on financial performance of commercial banks in Nigeria. In achieving these objectives, the study collects a 7-years' time-series data from corporate annual report and financial statements for the period 2009-2015. The choice of the years is the data availability for most of the banks during this period. Meanwhile, few banks have liquidated while some were established during this period. The selected commercial banks are listed financial institutions in the Nigerian Stock Exchange (NSE). Using this report, the study selects a total of sixteen Nigerian commercial banks. The choice of the banking sector is based on the pivotal role of the banking industry in triggering a financial crisis. The data used for this study are limited to annual reports, which are readily available at the Central Bank of Nigeria Statistical Database online and applies to commercial banks in Nigeria. However, the study focused on the financial risk faced by commercial banks in Nigeria, and their financial performance was aimed at addressing the challenge of ever emerging risks within the sector. It was an attempt to critically examine the various practices through which commercial banks manage various types of risks that they face, and then determine the relationship that exists between financial risk and the financial performance of banks. This study, therefore, sought to fill the gap in knowledge on the effects of financial risks on financial performance of commercial banks in Nigeria.